Pembangunan Sistem Freelance Marketplace Untuk Bidang Pengembangan Perangkat Lunak Berbasis Web - Arka Fadila Yasa; Denny Sagita Rusdianto; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The growth of the information technology sector in Indonesia is relatively fast and will continue to grow, it affects the way a company to meet the needs of human resources to complete a project. Freelancers is one solution for project owners who want employees to meet the needs of human resources. One important factor to determine the success of projects done by freelancers is to recruit the right people to work on the project, but there is a problem because clients need to compare the profiles of freelancers to one another. In the purpose to simplify the recruitment process, the authors took the initiative to create a system to bring together those who are in need of freelancers to work on a project with freelancers who have expertise with focus on finding workers in the field of software development. System are restricted to serve in the field of software development is because the need for freelancers in that field is the greatest one. Based on the results of the needs analysis sourced from the results of the elicitation of needs using the observation method of a similar system that already exists, obtained fifty functional system requirements, then the results of system design there are twenty-one system classes to be implemented. The results of the system testing that have been completed are implemented consisting of unit testing, integration testing, validation testing, and compatibility testing showing that the system can run as needed and is capable of running on various web browsers.